Surface cobaltization for boosted kinetics and excellent stability of nickel-rich layered cathodes - Zhang Qiusheng; Cui Chunyu; Chen Hao; Pan Shuaijun; Zhang Yinghe; Zhu Jian; Lu Bingan (National Science Open)
The feasibility of LiNi0.6Co0.2Mn0.2O2 as a primary cathode material has decreased due to the fragile cobalt (Co) supply chain and its undesirable effects on structural degradation. LiNi0.6Mn0.4O2 deserves greater attention because of its high thermal and cyclic stability, coupled with low raw material and production costs. However, this material suffers from low reversible capacity and poor rate performance. Herein, we rationally design a high-performance cathode structure composed of a robust conductive protective layer, gradient Li+ ions conductive layer and stable bulk phase of LiNi0.6Mn0.4O2 through surface cobaltization, which not only boosts the reaction kinetics of the electrode but also suppresses particle cracking and mitigates surface structural degradation. As a result, a dramatically improved rate capacity (118.7 vs 53.5 mAh g−1 at 5 C) and impressive capacity retention after 300 cycles (90.4% in a full cell) at a high cutoff voltage (4.4 V) are obtained. Co-modified LiNi0.6Mn0.4O2 is promising to challenge commercial position of LiNi0.6Co0.2Mn0.2O2 attributed to the accessible capacity, superior rate capacity, excellent cycle performance, good thermal stability and low cost. Our results open a door for optimizing the use of Co and the structural design of high-nickel cathodes.